The causes and consequences of perceptions of election unfairness - Sedziaka, Alesia A (ProQuest Dissertations & Theses, 2014)
The role of unfair elections in breakdown or maintenance of electoral authoritarian regimes has been subject to debate in recent research. On the one hand, the conduct of elections may serve to enhance popular legitimacy and deter challenges to the regime. On the other hand, electoral manipulation may contribute to grievances that fuel mass protest. However, empirical research on the consequences of electoral manipulation for popular support has been limited by the availability of appropriate survey data and has mostly focused on summary or process-based assessments of electoral unfairness. The premise of this study is that electoral manipulation is difficult to assess due to its inherent complexity and ambiguity. As a result, citizens are likely to use cognitive shortcuts to interpret electoral manipulation. Applying psychological theories of justice and motivated political reasoning in this context, this project aims to investigate how both process- and outcome-based assessments of election unfairness influence summary judgments of election quality, regime support, and support for electoral protest. It further seeks to determine how voters' political preferences bias, or condition, the impact of election unfairness evaluations. These propositions are tested using novel data from the XIX New Russia Barometer survey, conducted shortly after the controversial 2011 Russian State Duma election that triggered mass electoral protests. This study finds that perceived election outcome unfairness affects reactions to elections alongside assessments of the electoral process; it also shows evidence of partisan reasoning in evaluations of election unfairness. Ultimately, this project points to some factors that may explain the diverging consequences of electoral manipulation for popular support.